Transmission of Swine Influenza A Viruses along Pig Value Chains, Cambodia, 2020–2022 - Arata Hidano; Dina Koeut; Hannah Holt; William T.M. Leung; Sokhom Krean; Vutha Chhim; Bunnary Seng; Sovanncheypo Chao; Wong Foong Ying; Pov Son; Sina Vor; Sokchea Huy; et al. (Emerging Infectious Diseases, 2024)
We analyzed >4,000 pig samples from slaughterhouses in Cambodia and found higher influenza A seroprevalence (40.0%) and prevalence (1.5%) among pigs from commercial farms than smallholder farms (seroprevalence 8.9%; prevalence 0.6%). Multivariable analyses revealed evidence of transmission after leaving farms. Findings have implications for influenza risk and surveillance in emerging livestock systems.